Laser-induced breakdown spectroscopy experimentation and applications - Haider, Zuhaib; Tufail, Kashif; Roslan, Sufi; Munajat, Yusof (Penerbit UTHM, 2020)
This is an era of rapid production and fast growth. Reliable and fast analytical testing techniques are an essential part of manufacturing industries and testing and certifying authorities. Laser-Induced Breakdown Spectroscopy (LIBS) is one of the highly potential techniques to compete in this competitive arena for rapid elemental analysis which can be further used for real-time composition monitoring in the production line, post-production inspection, scrap sorting and even for classification of biological samples. In addition, remote and stand-off modes of operation increase the application potential of LIBS by many folds. It can be deployed in physically inaccessible or potentially unsafe areas. Compact LIBS systems have made its portability possible which implies ease of in-situ deployment.